Whey Protein Supplementation Preserves Postprandial Myofibrillar Protein Synthesis during Short-Term Energy Restriction in Overweight and Obese Adults. Issue 2 (17th December 2014) - Hector, Amy J; Marcotte, George R; Churchward-Venne, Tyler A; Murphy, Caoileann H; Breen, Leigh; von Allmen, Mark; Baker, Steven K; Phillips, Stuart M
Abstract: Background: Higher dietary energy as protein during weight loss results in a greater loss of fat mass and retention of muscle mass; however, the impact of protein quality on the rates of myofibrillar protein synthesis (MPS) and lipolysis, processes that are important in the maintenance of muscle and loss of fat, respectively, are unknown. Objective: We aimed to determine how the consumption of different sources of proteins (soy or whey) during a controlled short-term (14-d) hypoenergetic diet affected MPS and lipolysis. Methods: Men ( n = 19) and women ( n = 21) (age 35–65 y; body mass index 28–50 kg/m 2 ) completed a 14-d controlled hypoenergetic diet (−750 kcal/d). Participants were randomly assigned, double blind, to receive twice-daily supplements of isolated whey (27 g/supplement) or soy (26g/supplement), providing a total protein intake of 1.3 ± 0.1 g/(kg · d), or isoenergetic carbohydrate (25 g maltodextrin/supplement) resulting in a total protein intake of 0.7 ± 0.1 g/(kg · d). Before and after the dietary intervention, primed continuous infusions of L-[ring- 13 C6 ] phenylalanine and [ 2 H5 ]- glycerol were used to measure postabsorptive and postprandial rates of MPS and lipolysis. Results: Preintervention, MPS was stimulated more ( P < 0.05) with ingestion of whey than with soy or carbohydrate. Postintervention, postabsorptive MPS decreased similarly in all groups (all P < 0.05). Postprandial MPS was reduced by 9 ± 1% in the whey group, which was less ( P < 0.05) than the reduction in soy and carbohydrate groups (28 ± 5% and 31 ± 5%, respectively; both P < 0.05) after the intervention. Lipolysis was suppressed during the postprandial period ( P < 0.05), but more so with ingestion of carbohydrate ( P < 0.05) than soy or whey. Conclusion: We conclude that whey protein supplementation attenuated the decline in postprandial rates of MPS after weight loss, which may be of importance in the preservation of lean mass during longer-term weight loss interventions. This trial was registered at clinicaltrials.gov as NCT01530646.